Aspects of stability for multicriteria quadratic problems of Boolean programming - Vladimir A.Emelichev; Yury V.Nikulin (Moldova, Republic of, 2022)
We consider a multicriteria Boolean programming problem of finding the
Pareto set. Partial criteria are given as quadratic functions, and they are exposed
to independent perturbations. We study quantitative characteristic of stability (stability
radius) of the problem. The lower and upper bounds for the stability radius
are obtained in the situation where solution space and problem parameter space are
endowed with various H¨older’s norms.